Kansas Fertilizer Research 2020 - D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
A summary of research conducted in 2018-2020 on fertilizer use and management practices for crops in Kansas. Published in 2020 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Servicehttps://www.ag.k-state.edu/.
Keywords: fertilizer; tillage; nitrogen; phosphorus; irrigation; sorghum; wheat; sulfur; corn; soybean